Emphysematous pyelonephritis and orchiepididymitis due to Mycobacterium tuberculosis in a kidney transplant recipient - José J. Gutiérrez-Hernández; Carolina Covarrubias-Castellón; Renato Parra-Michel; Francisco Fuentes-Ramírez; Karen I. Cortés-Montenegro; Sergio E. Martínez-Ortiz; Paola K. Larios-Fernandez; Hugo B. Espinoza; Juan O. Romero-Tafoya; David A. Juárez-Flores; María E. Gallardo-Rodríguez; Brenda G. Rosales-Torres; et al. (Nefrología Latinoamericana)
Tuberculosis may present with extrapulmonary manifestations, 30-40% of which involve the genitourinary tract. The incidence of tuberculosis in kidney recipients is 20-74 times higher than in the general population. We present the case of a patient with a renal graft transplanted 10 years prior, who developed emphysematous pyelonephritis, treated with conservative management, associated with chronic orchiepididymitis due to Mycobacterium tuberculosis, resolved with radical orchiectomy.